2021
DOI: 10.5761/atcs.oa.20-00364
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Renal Protective Effect of Tolvaptan in Chronic Kidney Disease Patients after Open-Heart Surgery

Abstract: Purpose: Unlike loop diuretics, tolvaptan is reported to have a renal protective effect. The purpose of this study was to retrospectively assess the efficacy of tolvaptan administration in chronic kidney disease (CKD) patients following open-heart surgery. Methods: From February 2017 to August 2020, 75 patients with preoperative CKD stages IIIb-V were enrolled in this study and were divided into two groups: the control group (n = 30) and the tolvaptan group (n = 45). All patients routinely received conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The efficacy of TLV has been reported for patients with CKD in other studies[ 7 , 8 ]. Recently, the administration of TLV also demonstrated that it decreased the worsening of renal function[ 9 , 10 ]. Furthermore, TLV therapy was more effective in maintaining renal function than treatment with increasing doses of loop diuretics because TLV has a strong diuretic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of TLV has been reported for patients with CKD in other studies[ 7 , 8 ]. Recently, the administration of TLV also demonstrated that it decreased the worsening of renal function[ 9 , 10 ]. Furthermore, TLV therapy was more effective in maintaining renal function than treatment with increasing doses of loop diuretics because TLV has a strong diuretic effect.…”
Section: Introductionmentioning
confidence: 99%